A Behavioral Approach to Compliance: OSHA Enforcement's Impact on Workplace Accidents - John T. Scholz
This study test for effects of OSHA enforcement, using data on injuries and OSHA inspections for 6,842 manufacturing plants between 1979 and 1985. We use measures of general deterrence (expected inspections at plants like this one) and specific deterrence (actual inspections at this plant). Both measures of deterrence are found to affect accidents, with a 10% increase in inspections with penalties predicted to reduce accidents by 2%. The existence of specific deterrence effects, the importance of lagged effects, the asymmetrical effects of probability and amount of penalty on accidents, and the tendency of injury rates to self-correct over a few years support a behavioral model of the firm's response to enforcement rather than the traditional expected penalty' model of deterrence theory.